Insights Into the Role of Platelet-Derived Growth Factors: Implications for Parkinson’s Disease Pathogenesis and Treatment - Li, Dan; Huang, Le-Tian; Zhang, Cheng-pu; Li, Qiang; Wang, Jia-He (Frontiers in Aging Neuroscience, 2022)
Parkinson's disease (PD), the second most common neurodegenerative disease after Alzheimer’s disease, commonly occurs in the elderly population, causing a significant medical and economic burden to the aging society worldwide. At present, there are few effective methods that achieve satisfactory clinical results in the treatment of PD. Platelet-derived growth factors (PDGFs) and platelet-derived growth factor receptors (PDGFRs) are important neurotrophic factors that are expressed in various cell types. Their unique structures allow for specific binding that can effectively regulate vital functions in the nervous system. In this review, we summarize the possible mechanisms by which PDGFs/PDGFRs regulate the occurrence and development of PD by affecting oxidative stress, mitochondrial function, protein folding and aggregation, Ca2+ homeostasis, and cell neuroinflammation. These modes of action mainly depend on the type and distribution of PDGFs in different nerve cells. We also summarize the possible clinical applications and prospects for PDGF in the treatment of PD, especially in genetic treatment. Recent advances show that PDGFs have contradictory roles within the central nervous system (CNS). Although they exert neuroprotective effects through multiple pathways, they are also associated with the disruption of the blood–brain barrier (BBB). Our recommendations based on our findings include further investigating the contradictory neurotrophic and neurotoxic effects of the PDGFs acting on the CNS.